A20 is critical for the induction of Pam3CSK4-tolerance in monocytic THP-1 cells. - Jinyue Hu; Guihua Wang; Xueting Liu; Lina Zhou; Manli Jiang; Li Yang (PLoS ONE, 2014)
A20 functions to terminate Toll-like receptor (TLR)-induced immune response, and play important roles in the induction of lipopolysacchride (LPS)-tolerance. However, the molecular mechanism for Pam3CSK4-tolerance is uncertain. Here we report that TLR1/2 ligand Pam3CSK4 induced tolerance in monocytic THP-1 cells. The pre-treatment of THP-1 cells with Pam3CSK4 down-regulated the induction of pro-inflammatory cytokines induced by Pam3CSK4 re-stimulation. Pam3CSK4 pre-treatment also down-regulated the signaling transduction of JNK, p38 and NF-κB induced by Pam3CSK4 re-stimulation. The activation of TLR1/2 induced a rapid and robust up-regulation of A20, suggesting that A20 may contribute to the induction of Pam3CSK4-tolerance. This hypothesis was proved by the observation that the over-expression of A20 by gene transfer down-regulated Pam3CSK4-induced inflammatory responses, and the down-regulation of A20 by RNA interference inhibited the induction of tolerance. Moreover, LPS induced a significant up-regulation of A20, which contributed to the induction of cross-tolerance between LPS and Pam3CSK4. A20 was also induced by the treatment of THP-1 cells with TNF-α and IL-1β. The pre-treatment with TNF-α and IL-1β partly down-regulated Pam3CSK4-induced activation of MAPKs. Furthermore, pharmacologic inhibition of GSK3 signaling down-regulated Pam3CSK4-induced A20 expression, up-regulated Pam3CSK4-induced inflammatory responses, and partly reversed Pam3CSK4 pre-treatment-induced tolerance, suggesting that GSK3 is involved in TLR1/2-induced tolerance by up-regulation of A20 expression. Taken together, these results indicated that A20 is a critical regulator for TLR1/2-induced pro-inflammatory responses.